2017
DOI: 10.1111/1750-3841.13689
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Oxidation Stability Evaluation of Tea Polyphenols‐Loaded Inverse Micro‐Emulsion

Abstract: Compared to synthetic antioxidants, tea polyphenols (TPs) has its own advantages in edible oil industry, however, the hydrophilic properties have restricted its applications. In this study, the ternary phase diagram of TPs-loaded micro-emulsion (ME) system was constructed, in which glyceryl monooleate (GMO), Tween80, linoleic acid as the surfactants, ethanol as the co-surfactant and soybean, corn, sunflower oil as the oil phase, have been used for the preparation of ME. The results indicated that a composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…With the oxidation of TP and GA, the antibacterial ability of NMs against P. aeruginosa and S. aureus was significantly reduced. This result is in line with a study which observed that the addition of TP can effectively retard oxidation in the three edible oils (corn, soybean, and sunflower) [ 28 ]. In addition, adding antioxidants to the emulsion can improve its storage stability of the emulsion.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…With the oxidation of TP and GA, the antibacterial ability of NMs against P. aeruginosa and S. aureus was significantly reduced. This result is in line with a study which observed that the addition of TP can effectively retard oxidation in the three edible oils (corn, soybean, and sunflower) [ 28 ]. In addition, adding antioxidants to the emulsion can improve its storage stability of the emulsion.…”
Section: Resultssupporting
confidence: 91%
“…Jiang et al showed that GA can improve the emulsion stability and thermal stability of microemulsions [ 21 ]. In addition, Lan et al showed that TP can improve the stability of microemulsions [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…As an indicator of the primary oxidation product, the POV was determined following the procedures outlined in the AOCS method CD-8-53(1998). 19 In a nutshell, we dissolved 2−3 g of the sample in a 30 mL solution of acetic acid−chloroform (3:2, v/v), supplemented with 1 mL of saturated KI. The mixture was then mixed for 5 min before adding 100 mL of water.…”
Section: Oxidation Measurement Of Lipid Hydroperoxidesmentioning
confidence: 99%
“…POVs of the emulsions were measured after storage for 0, 1, 3, 5, 7, and 15 days at room temperature in the dark, according to the AOCS standard procedure Cd-8-53 [56,57]. Briefly, approximately 2 mL of the sample was mixed with 30 mL acetic acid-chloroform (3:2, v/v) and 1 mL saturated KI.…”
Section: Measurement Of Peroxide Value (Pov)mentioning
confidence: 99%